(untitled) (Third Sector Social Economic Review, 2025)
Social policies which are implemented by the state to protect individuals against social risks, and they are also policies that have inclusive and integrative features. While the working class formed with the industrial revolution constitutes the basis of both social policy sense and social security in a narrow sense, at the same time, the high rate of “dependent workers” in the working population has been effective in the development of social policies. In the recent period, with the encouragement of enterprise, the 2008 crisis, the pandemic process and the gig economy, the self-employed population has further intensified. It is a prominent area that manifests itself with some atypical forms of employment, and it is normal for self-employed workers to be exposed to social risks and therefore to the risk of unemployment like all other dependent workers. The main objective of the study is to explain the unemployment insurance practice of independent workers, which can be described as a significant gap, by referring to the historical process of labour and employee statuses from the industrial revolution to the present day, also by referring to the country characteristics of different regimes. In Turkey, some statistical information on employee statuses is given in comparison with different countries and it is concretized that the need for unemployment of independent workers has become apparent. Law No. 4447, which encompasses voluntary social insurances and finally the regulations introduced with the application of “tradesmen and ahilik fund” which has adherence with self-employed have been mentioned. By concretizing the practices provided by unemployment insurance and comparing the practices in different countries, the future reflections of the practice, which has features such as premium requirement, amount and duration of benefits, have been analyzed in the study.